Modification of structural and electrical properties of Ca element on barium titanate nano-material synthesized by hydrothermal method. (18th November 2017) - Shandilya, Mamta; Rai, Radheshyam; Zeb, Aurang; Kumar, Shammi
ABSTRACT: Ba1-x Cax TiO3 (x = 0.10, 0.15, 0.20 and 0.25) ceramics were prepared by using standard Sol-Gel hydrothermal reaction technique at 150°C. Structural and dielectric properties were carry out by using X-ray diffraction and dielectric constant, tangent loss and conductivity measurements. Single-phase perovskite-type X-ray diffraction patterns were observed and the samples have a phase with a tetrahedral structure at room temperature for all the compositions. SEM image of Ba1-x Cax TiO3 powder shows inhomogeneity with the increment of Ca element. Small grains with average grain sizes of ∼20 ± 5 nm uniformly distributed over the mesocrystals. The temperature dependence of the dielectric permittivity of tetrahedral Ba1-x Cax TiO3 ceramic as a function of frequency (1 kHz-100 kHz) at different temperature (RT–300°C) provided useful information on electrical behavior (Ferroelectric-Relaxor relationship). The behavior of the dielectric graph (in paraelectric region) confirmed the relaxor behavior of the material at high temperature (160–300°C) range. Nature of diffusivity graph also indicating that, increase of Ca content improved the diffusivity of materials. Values of Tm increased with increasing x = 0.10– 0.25, from ∼120°C to 140°C. In the comparison of other, the composition Ba0.90 Ca0.10 TiO3 reveals strong results. It has dielectric permittivity (ϵ) 5741 ± 200 at the low value of loss tanδ = 0.009 ± .091 along with the transition temperature (Tc ) at ∼131 ± 2 shows diffusivity 1.72 ± 10 < 2 and activation energy 0.821 ± .030.